2020
DOI: 10.1002/htj.21961
|View full text |Cite
|
Sign up to set email alerts
|

Effect of suction on the stagnation point flow of hybrid nanofluid toward a permeable and vertical Riga plate

Abstract: The application of appropriate wall mass suction (transpiration) has been reported as the key factor to generate steady solutions in the opposing flow (shrinking or opposing buoyancy). This study features the impact of the suction and mixed convection parameters in the stagnation point flow toward a permeable Riga plate. Due to the capability of hybrid nanofluids in enhancing the heat transfer performance, the combination of copper (Cu) and alumina (Al2O3) nanoparticles are used, including water as the base fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In his valuable study, the stability of the prepared nanofluids was determined by measuring the pH of the nanofluids and the nanofluid stability was found to diminish with increasing volume concentration. The values of 6.0 M = is used based on the work done by Turkyilmazoglu et al, [28] to ensure the existence of the dual solution while Pr 6.2 = is implemented so that the results are compatible with the water-based nanofluid [11][12].…”
Section: Results Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…In his valuable study, the stability of the prepared nanofluids was determined by measuring the pH of the nanofluids and the nanofluid stability was found to diminish with increasing volume concentration. The values of 6.0 M = is used based on the work done by Turkyilmazoglu et al, [28] to ensure the existence of the dual solution while Pr 6.2 = is implemented so that the results are compatible with the water-based nanofluid [11][12].…”
Section: Results Interpretationmentioning
confidence: 99%
“…In another study, Takabi and Salehi [8] found out that the use of hybrid nanofluid increases the heat transfer efficiency, resulting in improved cooling efficiency and lower heated surface temperature. Since then, the study of nanofluid and hybrid nanofluid has attracted interest from many researchers considering various effects [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…À0.1 # Z # À0.5 À 0.1 # « # À0 and 0.5 # d # 1.0 to guarantee that the provided solutions are consistent. As there is no specific experiment was conducted, the parameter values were chosen based on the values established by previous researchers to ensure the dual solutions' existence (Khashi'ie et al, 2020(Khashi'ie et al, , 2021Nasir et al, 2019). Furthermore, the selection of h 1 = 10 ensured that all numerical solutions were approaching asymptotic values accurately.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Nasir et al (2019) performed an analysis towards a stagnation point flow past a permeable Riga plate in a viscous fluid, while Hayat et al (2016) studied the boundary layer flow properties of nanofluid by varying the variable thickness in a Riga plate. Khashi'ie et al (2020Khashi'ie et al ( , 2021 are concerned with the suction effects on the stagnation point of hybrid nanofluid flow over a vertical Riga plate. Their studies demonstrated that the hybrid nanofluid surpasses the nanofluid in terms of thermal performance.…”
Section: Introductionmentioning
confidence: 99%
“…There is only a slight of difference between the numerical values using both correlations as discussed by Xu [10] and Khashi'ie et al, [11]. A detail comparison of the published papers with different types of correlations was initiated and discussed by Khashi'ie et al, [12]. The numerical exploration of dual solutions in hybrid nanofluid flow is not only limited to a flat plate surface, but also have been actively investigated for a thin needle, circular cylinder, disk, Riga plate and curved surface .…”
Section: Introductionmentioning
confidence: 99%